2008
DOI: 10.1016/j.bpc.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for confirming sequence periodicity identified by Fourier transform analysis: Application to GCR2, a candidate plant GPCR?

Abstract: . Criteria for confirming sequence periodicity identified by Fourier transform analysis: application to GCR2, a candidate plant GPCR?. Biophysical Chemistry, Elsevier, 2008, 133 (1-3) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 55 publications
(55 reference statements)
0
37
0
3
Order By: Relevance
“…Indeed, the pitfalls of GPCR identification are illustrated by the high profile (Liu et al, 2007) but erroneous identification of GCR2 as a plant GPCR. It has now been confirmed through crystallization that GCR2 is a lantibiotic cyclase-like protein , as predicted by our fold recognition studies (Illingworth et al, 2008).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Indeed, the pitfalls of GPCR identification are illustrated by the high profile (Liu et al, 2007) but erroneous identification of GCR2 as a plant GPCR. It has now been confirmed through crystallization that GCR2 is a lantibiotic cyclase-like protein , as predicted by our fold recognition studies (Illingworth et al, 2008).…”
mentioning
confidence: 69%
“…The negative controls were AAU04564.1 Halobiforma lacisalsi (bacteriorhodopsin) and AT2G20770 (Arabidopsis [Arabidopsis thaliana] GCL2 GCR2). Bacteriorhodopsin is a 7TM protein but not a GPCR, while GCR2 has seven hydrophobic helical motifs that are almost long enough to span the membrane, so that its homologs were initially erroneously identified as GPCRs (Illingworth et al, 2008). These sequences were submitted to the following fold recognition servers: I-TASSER (Roy et al, 2010), FUGUE (Shi et al, 2001), Phyre (Bennett-Lovsey et al, 2008), genTHREADER (Jones, 1999a), mgenTHREADER (McGuffin andJones, 2003), HHpred (Söding et al, 2005), LOMETS (Wu and Zhang, 2007), and MUSTER (Wu and Zhang, 2008).…”
Section: Fold Recognitionmentioning
confidence: 99%
“…58 However, it is important to mention that the characterization of GCR2 as a GPCR and ABA receptor is still a matter of discussion. [59][60][61] More recently, other GPCR-like proteins (GTG1 and GTG2) were identified and its characterization revealed that the GTG proteins represent a novel class of proteins with topology similar to GPCRs but with classic GTP-binding/GTPase activity. 62 Further analysis providing biochemical and phenotypic evidences suggest that GTG1 and GTG2 proteins are redundantly involved in G protein-coupled ABA signaling and are, or are parts of, ABA receptor complexes 62 and their detailed characterization will likely clarify the mechanism underlying the ABA response.…”
Section: Co 2 and Stomatal Developmentmentioning
confidence: 99%
“…Otro supuesto receptor de ABA aislado, GCR2, se propuso también como un receptor acoplado a proteínas G. Actualmente existe cierta controversia acerca tanto sobre su papel en la señalización por ABA [59,70] como en su inclusión en el grupo de receptores acoplados a proteínas G [87,97]. Por un lado esta proteína muestra cierta similitud con una enzima soluble de bacterias de la superfamilia LanC (lantibiotic synthetase component C) [97].…”
Section: Y Enunclassified
“…Se han identificado muchos de los componentes de la ruta de señalización y se ha estudiado la interconexión existente entre ellos para elucidar la estructura de la cascada de señalización del ABA. Estudios de genética molecular, bioquímica y farmacología han llevado a la identificación de más de 100 loci y numerosos mensajeros secundarios que participan en la ruta Otro supuesto receptor de ABA aislado, GCR2, se propuso también como un receptor acoplado a proteínas G. Actualmente existe cierta controversia acerca tanto sobre su papel en la señalización por ABA [59,70] como en su inclusión en el grupo de receptores acoplados a proteínas G [87,97]. Por un lado esta proteína muestra cierta similitud con una enzima soluble de bacterias de la superfamilia LanC (lantibiotic synthetase component C) [97].…”
unclassified